Thrombocytopenia in Liver Disease - Markus Peck-Radosavljevic (Canadian Journal of Gastroenterology)
Moderate thrombocytopenia is a frequent finding in cirrhosis of the liver and well tolerated in most instances. The pathophysiology of thrombocytopenia in liver disease has long been associated with the concept of hypersplenism, where portal hypertension was thought to cause pooling and sequestration of all corpuscular elements of the blood, predominantly thrombocytes in the enlarged spleen. The concept of hypersplenism was never proven beyond any doubt but was widely accepted for the lack of alternative explanations.